Middle-aged women’s experiences of physical activity for managing menopausal symptoms: a phenomenological study - Hee Jung Cho; Sukhee Ahn (Korean Journal of Women Health Nursing, 2023)
Purpose The purpose of this study was to comprehensively understand and describe the meaning of physical activity for managing menopausal symptoms in middle-aged women. Methods This study targeted middle-aged women with menopausal symptoms who participated in regular exercise at least three times a week for more than 12 weeks. Nine participants were individually interviewed via in-depth face-to-face interviews, and participatory observation was also employed. Colaizzi’s phenomenological qualitative research method was applied for analysis. Results Participants were asked, “What does it means to participate in physical activity at this time of your life?” Fourteen codes, six themes, and three theme clusters were derived for the meaning of physical activity for managing menopausal symptoms in these middle-aged women. The six themes were “reviving the exhausted body and mind,” “being free from the yoke of pain,” “being settled in life,” “finding oneself and becoming altruistic,” “striving while anticipating change,” and “equipping the body and mind.” The three theme clusters were “overcoming my past pain,” “taking the initiative for today’s life,” and “moving towards new change.” Conclusion The narratives revealed that physical activity allowed women to overcome menopausal symptoms, the burden of relationships, and stress, thereby enabling them to make positive changes in their lives and have expectations for the future. Thus, physical activity was a positive force in a healthy menopausal transition for women with menopausal symptoms. The findings of this study can be used to encourage physical activity in peri-menopausal women and to develop physical activity programs for managing menopausal symptoms.